(untitled) (ENTHYMEMA, 2019)
In “Hermeneutics and the Cognitive Sciences,” which is proposed here in translation, Shaun Gallagher considers the possible relations between hermeneutics and the cognitive sciences, focusing on the points on which the two perspectives of investigation agree and on mutual contributions that each could provide to the other. Particular attention is given to the discussion of the characteristics of intersubjective understanding, considering both Diltheyan thought and the most recent results of the study of subjectivity within the field of the cognitive sciences. The article is preceded by an introduction which, in addition to presenting the most important aspects of Gallagher’s argumentation, aims to highlight some of the outcomes of the current debate on the interdisciplinarity between humanities, on one side, and cognitive sciences and neuroscience, on the other.